Regulation of DNA Repair Fidelity by Molecular Checkpoints: “Gates” in DNA Polymerase β's Substrate Selection - Radhakrishnan, Ravi; Arora, Karunesh; Wang, Yanli; Beard, William A; Wilson, Samuel H; Schlick, Tamar (Biochemistry (Easton), 2006)
With an increasing number of structural, kinetic, and modeling studies of diverse DNA polymerases in various contexts, a complex dynamical view of how atomic motions might define molecular “gates” or checkpoints that contribute to polymerase specificity and efficiency is emerging. Such atomic-level information can offer insights into rate-limiting conformational and chemical steps to help piece together mechanistic views of polymerases in action. With recent advances, modeling and dynamics simulations, subject to the well-appreciated limitations, can access transition states and transient intermediates along a reaction pathway, both conformational and chemical, and such information can help bridge the gap between experimentally determined equilibrium structures and mechanistic enzymology data. Focusing on DNA polymerase β (pol β), we present an emerging view of the geometric, energetic, and dynamic selection criteria governing insertion rate and fidelity mechanisms of DNA polymerases, as gleaned from various computational studies and based on the large body of existing kinetic and structural data. The landscape of nucleotide insertion for pol β includes conformational changes, prechemistry, and chemistry “avenues”, each with a unique deterministic or stochastic pathway that includes checkpoints for selective control of nucleotide insertion efficiency. For both correct and incorrect incoming nucleotides, pol β's conformational rearrangements before chemistry include a cascade of slow and subtle side chain rearrangements, followed by active site adjustments to overcome higher chemical barriers, which include critical ion−polymerase geometries; this latter notion of a prechemistry avenue fits well with recent structural and NMR data. The chemical step involves an associative mechanism with several possibilities for the initial proton transfer and for the interaction among the active site residues and bridging water molecules. The conformational and chemical events and associated barriers define checkpoints that control enzymatic efficiency and fidelity. Understanding the nature of such active site rearrangements can facilitate interpretation of existing data and stimulate new experiments that aim to probe enzyme features that contribute to fidelity discrimination across various polymerases via such geometric, dynamic, and energetic selection criteria.